Molecular epidemiology of Pseudomonas aeruginosa isolated from infected ICU patients: a French multicenter 2012–2013 study - Slekovec, Céline; Robert, Jérôme; van der Mee-Marquet, Nathalie; Berthelot, Philippe; Rogues, Anne-Marie; Derouin, Véronique; Cholley, Pascal; Thouverez, Michelle; Hocquet, Didier; Bertrand, Xavier (European journal of clinical microbiology & infectious diseases, 2019)
Although Pseudomonas aeruginosa has a non-clonal epidemic population structure, recent studies have provided evidence of the existence of epidemic high-risk clones. The aim of this study was to assess the molecular epidemiology of P. aeruginosa isolates responsible for infections in French ICUs, regardless of resistance patterns. For a 1-year period, all non-duplicate P. aeruginosa isolated from bacteremia and pulmonary infections in ten adult ICUs of six French university hospitals were characterized by antimicrobial susceptibility testing and genotyping (MLST and PFGE). We identified β-lactamases with an extended spectrum phenotypically and by sequencing. The 104 isolates tested were distributed in 46 STs, of which 7 epidemic high-risk (EHR) clones over-represented: ST111, ST175, ST235, ST244, ST253, ST308, and ST395. Multidrug-resistant (MDR) isolates mostly clustered in these EHR clones, which frequently spread within hospitals. Only one ST233 isolate produced the carbapenemase VIM-2. PFGE analysis suggests frequent intra-hospital cross-transmission involving EHR clones. For ST395 and ST308, we also observed the progression from wild-type to MDR resistance pattern within the same PFGE pattern. Molecular epidemiology of P. aeruginosa in French ICUs is characterized by high clonal diversity notably among antimicrobial susceptible isolates and the over-representation of EHR clones, particularly within MDR isolates, even though multidrug resistance is not a constant inherent trait of EHR clones.